x(x+2)=-1

Simple and best practice solution for x(x+2)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+2)=-1 equation:


Simplifying
x(x + 2) = -1

Reorder the terms:
x(2 + x) = -1
(2 * x + x * x) = -1
(2x + x2) = -1

Solving
2x + x2 = -1

Solving for variable 'x'.

Reorder the terms:
1 + 2x + x2 = -1 + 1

Combine like terms: -1 + 1 = 0
1 + 2x + x2 = 0

Factor a trinomial.
(1 + x)(1 + x) = 0

Subproblem 1

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Solution

x = {-1, -1}

See similar equations:

| (2x+4)=(6x-20) | | 16x^2-72x=81 | | log(3x-5)16=2 | | 20+4x=200 | | v/4+13=8 | | x^4-4x^3+10x=0 | | -19+(-13)+22= | | 33/12 | | 3x-4=9/3 | | 3ab(4a+b^2)= | | 42x=163/4 | | 8/17=x/24 | | 10/11=x/47 | | 5x=25/5 | | 3n+4=4n-1 | | x/45=4/20 | | 5/2r+7-2x+1=12 | | 5/2r+7o-2x+1=12 | | x/45=16/72 | | 3x=3/3 | | x/63=10/90 | | 12/30=18/x | | x(4)*x(-2)=x | | 30/42=15/x | | 3/12=7/24 | | m-4n/36m+m+5n/36m | | x^5+9x^5=0 | | 3/12=6/24 | | (8x-6)(7x+1)=0 | | 21/28=16/20 | | 184x=18x | | x-20+3x=180 |

Equations solver categories